Industrial Hemp—an Old but Versatile Bast Fiber Crop. Issue 13 (1st December 2022) - Zhao, Xinlin; Wei, Xiuye; Guo, Yuan; Qiu, Caisheng; Long, Songhua; Wang, Yufu; Qiu, Huajiao
ABSTRACT: Industrial hemp ( Cannabis sativa L.), as one of the most important traditional natural fiber crops, had almost been forgotten for the last several decades. However, an unprecedented opportunity has emerged for planting this crop due to its multiple uses and products derived from the plant as well as its quick-growing and strong adaptability to a wide range of agro-environmental conditions. Furthermore, the decision from the United Nations' Commission for Narcotic Drugs that removing medicinal cannabis from a category of dangerous drugs (Schedule IV of the Single Convention on Narcotic Drugs, 1961) in December 2020 has also greatly promoted the hemp's revival. Nowadays, industrial hemp has many agro-industrial applications, such as agriculture, textiles, papermaking, construction, bio-fuel. This review analyzes the current hemp production status throughout the world and outlines the main applications of industrial hemp in different fields. The outlook and the remaining questions that need to be solved in the future for the better development of industrial hemp were also discussed, such as how to promote the hemp planting in more broad regions, how to obtain high yields of aim products, and how to fully explore its usages in the future.